The Theoretical Description for Electrochemical Hydroxyquinol and Phloroglucinol Electrochemical Detection Over CoO(OH)-Modified Electrode - Tkach, V. V.; Kushnir, M. V.; de Oliveira, S. C.; Sydorchuk, L. P.; Kryvetskyi, V. V.; Kryvetska, I. I.; Kryvetskyi, I. V.; Sarkisova, Yu. V.; Yagodynets', P. I.; da Silva, A. O.; Derevianko, N. P.; Zavhorodnii, M. P.; et al. (My University, 2024)
Abstract: The theoretical description for hydroxyquinol and phloroglucinol electrochemical determination in food and wastewater has been made in this work. The efficiency of the cobalt (III) oxyhydroxide for this determination is verified from either an electroanalytical or electrosynthetical point of view, as it also provides assisted electro(co)polymerization. The stable steady-state is easy to obtain and maintain, confirming the electrode modifier's efficiency and the easy interpretation of curves for direct and indirect determination. This process may also efficiently remove phenolic compounds from the pharmaceutical wastewater.
Keywords: hydroxyquinol; phloroglucinol; cobalt (III) oxyhydroxide; electrochemical sensors; electrochemical oscillations; stable steady-state